Case Report: Whole genome sequencing identifies CCDC88C as a novel JAK2 fusion partner in pediatric T-cell acute lymphoblastic leukemia - Krstic, Aleksandra; Rezayee, Fatemah; Saft, Leonie; Hammarsjö, Anna; Svenberg, Petter; Barbany, Gisela (Frontiers in Pediatrics, 2023)
In the present report, we applied whole genome sequencing (WGS) to genetically characterize a case of pediatric T-cell acute lymphoblastic leukemia (ALL) refractory to standard therapy. WGS identified a novel JAK2 fusion, with CCDC88C as a partner. CCDC88C encodes a protein part of the Wnt signaling pathway and has previously been described in hematological malignancies as fusion partner to FLT3 and PDGFRB. The novel CCDC88C::JAK2 fusion gene results in a fusion transcript, predicted to produce a hybrid protein, which retains the kinase domain of JAK2 and is expected to respond to JAK2 inhibitors. This report illustrates the potential of WGS in the diagnostic setting of ALL.